Hydrogen bonding energy determined by molecular dynamics simulation and correlation to properties of thermoplastic starch films. (15th June 2017) - Yang, Jinhui; Tang, Kangkang; Qin, Guoqiang; Chen, Yanxue; Peng, Ling; Wan, Xia; Xiao, Huining; Xia, Qiuyang
Highlights: The molecular dynamics (MD) simulation method was used to investigate the hydrogen bonding energy of starch/glycerol system. The correlation between hydrogen bonding interaction and performances of thermoplastic starch materials was investigated in detail. The plasticized mechanism of starch can be interpreted from a microcosmic point of view according to the analytical results of the simulation. Abstract: The molecular dynamics (MD) simulation method was used to investigate the hydrogen bonding energy of starch/glycerol system under different temperatures (range from 90 °C to 120 °C) and different glycerol contents (range from 20% to 40%, based on dry starch weight). These effects on the hydrogen bonding energy (including the total hydrogen bonding energy, hydrogen bonding energy of starch/starch, glycerol/glycerol, and starch/glycerol) were analyzed in detail. Meanwhile, glycerol plasticized starch films were prepared using casting method. The relationship between the hydrogen bonding energy and the performances of thermoplastic starch film (TPSF), such as crystallinity, mechanical properties and water uptake determined experimentally, were revealed and discussed. The results indicated that glycerol/starch film contained strong hydrogen bonding interaction which could be increased by decreasing the temperature or increasing the glycerol content. The hydrogen bonding interaction is the key factor for the preparation of the plasticized starch material, and the plasticized mechanism can be interpreted according to the analytical results of the simulation.